A waste to energy technology for Enrichment of biomethane generation: A review on operating parameters, types of biodigesters, solar assisted heating systems, socio economic benefits and challenges. (April 2022) - Kalaiselvan, N.; Glivin, Godwin; Bakthavatsalam, A.K.; Mariappan, V.; Premalatha, M.; Raveendran, P. Saji; Jayaraj, S.; Sekhar, S. Joseph
Abstract: Anaerobic Digestion (AD) is one of the promising wastestoenergy (WtE) technologies that convert organic wastes to useful gaseous fuel (biogas). In this process methane is produced in the presence of methanogens (bacteria). The survival and activities of methanogens are based on several parameters such as pH, temperature, organic loading rate, types of biodigester. Moreover, these parameters influence the production of biogas in terms of yield and composition. Maintaining an appropriate temperaturefor AD is highly critical and energy intensive. This study reviews the various hybrid technologies assistedbio gas production schemes particularly from renewable energy sources. Also discuss the direct and indirect solar assisted bio-digester impacts and recommendation to improve its performance. In addition, the performance analysis Solar Photovoltaic (PV) and thermal collector assisted bio gas plants; besides their impact on the performance of anaerobic digesters. Since opportunities of solar energy are attractive, the effective utilization of the same is selected for the discussion. Besides, the various constraints that affect the yield and composition of biogas are also evaluated along with the current biogas technologies and the biodigesters. The environmental benefits, challenges and socio-economic factors are also discussed for the successful implementation of various technologies. Graphical abstract: Image 1 Highlights: The influencing parameters for biogas generation are discussed. Various pre-treatments are included to improve the biogas yield. Different types of biodigesters and its experimental methodologies are briefed. Socio economic benefits and challenges of solar assisted biodigesters are discussed. Various types of solar-assisted bio digesters are elaborated and its performance are compared with conventional biogas plant.